The Comprehensive Systematic Review of Association of the Glasgow Coma Scale (GCS) Score to Prognosis After Head Injury - Nabilah Safira; Melissa Theresia; Aurum Rizky Putri; Maydina Sifa Fauziah; Tri Wahyuni Puji Lestari; Dirga Filannira Desky; Ade Faisal (The International Journal of Medical Science and Health Research, 2025)
Introduction: The Glasgow Coma Scale (GCS) is a cornerstone in the initial assessment of traumatic brain injury (TBI), yet its precise prognostic value across diverse populations and clinical contexts remains nuanced. This systematic review synthesizes contemporary evidence on the association between GCS scores and prognosis after head injury. Methods: A comprehensive systematic review was conducted, screening studies based on predefined criteria including adult TBI populations, GCS assessment as a prognostic factor, and reported outcomes such as mortality or functional status (e.g., Glasgow Outcome Scale). Data from 80 included studies, encompassing over 2.3 million patients, were extracted regarding study design, population characteristics, GCS assessment details, outcomes, and moderating factors. Results: The evidence consistently demonstrates a strong negative association between lower GCS scores and worse outcomes. Meta-analyses revealed that patients with severe TBI (GCS 3-8) had dramatically higher mortality (OR 28.46) and lower odds of favorable outcomes (OR 0.03) compared to those with higher GCS (Karras et al., 2022). A clear dose-response relationship exists, particularly in elderly populations where mortality rates escalated from 12.3% (mild TBI) to 65.3% (severe TBI) (McIntyre et al., 2013). The GCS showed strong predictive accuracy for mortality (pooled AUC 0.90). However, its prognostic value is significantly moderated by age, timing of assessment, and the addition of clinical factors like pupillary reactivity, which improved predictive models (Marmarou et al., 2007; Vreeburg et al., 2024). Discussion: While GCS is a robust population-level predictor, its application for individual prognosis requires careful consideration of temporal dynamics, age-related effects, and injury severity subgroups. Early GCS assessments can be volatile, and significant recovery is possible even after severe initial presentations (McCrea et al., 2021). Multimodal assessment integrating GCS with pupillary response, CT findings, and age is essential for accurate prognostication. Conclusion: The GCS remains a fundamental, strongly prognostic tool in TBI. Clinicians must interpret GCS within a broader clinical context, employing multimodal models and recognizing that early scores should not solely dictate long-term prognostic judgments or limit therapeutic interventions, especially in salvageable subgroups.